Optimization of Turjawali Samapta Unit in Preventing Motor Vehicle Theft in Kendal Police Station - Infanisya, Devi Ristra (Advances in Police Science Research Journal, 2024)
The Kendal Resort Police in the Turjawali Samapta Unit patrol implementation has a significant role in maintaining public security and order and preventing the occurrence of the crime of motorized vehicle theft. Turjawali Samapta Kendal Police Unit patrols implementation has been going well, but motorized vehicle theft still happens with high case numbers. This situation prompted the author to research the problem of "Why is the implementation of patrols by the Turjawali Unit of the Samapta Unit in preventing the crime of motor vehicle theft at the Kendal Police Headquarters not yet optimal?". This final project aims to describe and analyze the implementation of patrols by the Turjawali Unit of the Samapta Unit in preventing criminal acts of motorized vehicle theft at the Kendal Police Headquarters and to describe and analyze the forms of optimizing patrols from the Turjawali Unit of the Samapta Unit in preventing criminal acts of motorized vehicle theft at the Kendal Police Headquarters. This research used a qualitative approach, using field research types by observing, interviewing informants, and studying documents. This study uses process management theory or POAC, SWOT theory, routine activity theory, and relevant concepts to the problem. There is the optimization concept, the patrol concept, the concept of motor vehicle theft, and the concept of Kamtibmas. The results of the study found that in carrying out the patrols of the Turjawali Samapta Unit of the Kendal Police, there were still some deficiencies in terms of planning, organizing, implementing, and supervising. Several things are not following Perkabaharkam Number 1 of 2017 concerning Patrols and SOP Patrols for the City of Kendal Police. Factors that influenced both internal and external caused the implementation Turjawali Unit of the Kendal Police Samapta Unit patrols cannot to run optimally. In this final assignment, the author will solve problems with problems found during research by referring to the Regulation of the Head of the National Police Security Maintenance Agency Number 1 of 2017 concerning Patrols.